Inovasi Pembelajaran Digital: Pelatihan Perancangan Media Pembelajaran Interaktif bagi Guru Sekolah Dasar - Lailiyah, Nur; Wijaya, Intan Prastihastari; Meyta Lusiana; Dewi Sholihatur Rohmah (Dedikasi Nusantara: Jurnal Pengabdian Masyarakat Pendidikan Dasar, 2024)
The rapid development of digital technology challenges and opportunities for elementary school teachers in developing more interactive and effective develop a more interactive and effective learning process. This community service activity aims to improve the competence of elementary school teachers in designing and developing interactive digital learning media that is with the needs of students in the digital era. This program was implemented at SDN Bangsal 3 by involving 15 teachers as participants. Activity implementation method includes training and mentoring which consists of three stages: (1) workshop introduction to various digital learning platforms and tools, (2) practical development of interactive learning media, and (3) evaluation and follow-up of implementation. implementation. The results of the activities show a significant increase in the ability of teachers in using digital technology for learning, as evidenced by: 85% of participants succeeded in developing at least one interactive digital learning media according to the subjects they teach, increased teacher confidence in integrating technology in learning, and confidence in integrating technology in learning, and the creation of 15 digital learning media products that are ready to be implemented. the creation of 15 digital learning media products that are ready to be implemented in the classroom. class. This activity has a positive impact in supporting the transformation of learning at the elementary school level towards learning that is more adaptive to the development of digital.